Model rapid application development dalam pengembangan sistem informasi pengarsipan surat - Harahap, Raihan; Muhammad Fadiga; Fadhli Rizqi Haidar Pane; Muhammad Siddik Hasibuan (Computer Science and Information Technology, 2023)
Archiving is essential in managing a collection of documents. Although archiving is now available in a web-based form, there are still agencies that use letter archives in a conventional way. This study was made to develop a web-based letter archive application for one of the government institutions in Medan, i.e. the Secretariat of the North Sumatra DPRD. This study uses two types of methods, namely research methods and system development methods. The research method used is a qualitative method with a research design in the form of observation and literature study. In addition, the system development method used is rapid application development (RAD). In addition, to design the application, researchers used XAMPP software to create MySQL as the database, JavaScript, PHP and Visual Studio Code as the programming language, as well as HTML and CSS to organize the web display. After that, the application is tested with the black box testing method. The results show that overall the features on the user function properly.